Islamic Development of Students at Boarding Schools Sirajul Walidain - Ilham Taufiq; Ade Halimah; Bagja Fajar Albiansyah; Imam Tabroni (Indonesian Journal of Applied and Industrial Sciences (ESA), 2022)
Pesantren education has its own curriculum in accordance with the objectives of the pesantren, the curriculum is structured by combining religious education as a provision of religious knowledge and general knowledge. On the other hand, the role of the santri administrator is very important for the santri. Management also helps in understanding Islamic religious education. This study aims to determine the important role of boarding school administrators in Islamic religious education. This study used qualitative research methods. The data collected in this study is based on the results of observations, interviews, and also documentation. The results of this study reveal that the board plays an important role in the sustainability of Islamic religious education in Islamic boarding schools. Because the administrators who are mandated by the caregivers must be responsible for the work program, the teaching and learning process takes place and the formation of students.